A STUDY ON DELEADING INFLUENCE TO ARSENIC DISTRIBUTION IN ANODE FURNACE OF PT. SMELTING GRESIK - DEUS PRIZFELIX (NIM 12102032), TITUS
Fire refining in the Mitsubishi process takes place in the anode furnace in order to remove impurities into slag. Dee-leading is a process to remove lead by adding flux, consisting of mixtures of silica and Cl-slag by certain composition, to the anode furnace. Some minor element should be retained in the copper metal at certain concentration because of its benefit in further process. Arsenic for example serves to prevent passivation in the electro-refining process. Distribution coefficient is used as a parameter to determine the influence of de-leading process on the final arsenic content. Distribution coefficient shows ratio between arsenic content in slag and copper respectively. This study shows that arsenic content was influenced by basicity of slag, oxidation level and oxygen partial pressure. The smallest distribution coefficient value was obtained aat basicity index of 0.36, 5257 ppm of dissolved oxygen, and 99.3% of copper grade at 1148oC.